Functional outcome of arterial thoracic outlet syndrome treatment - de Kleijn, Robert J. C. M. F.; Schropp, Ludo; Westerink, Jan; van Hattum, Eline S.; Petri, Bart-Jeroen; de Borst, Gert J. (Frontiers in Surgery, 2023)
INTRODUCTION The low prevalence of Arterial Thoracic Outlet Syndrome (ATOS) and diffuse symptomatology have resulted in limited data on optimal treatment strategies and long-term outcome. The aim of this study was to report and evaluate a single center experience with the treatment of ATOS including midterm patient reported outcome. METHODS All patients treated for ATOS from 2004 to 2020 were retrospectively identified. Patients were divided into two groups based on presenting symptoms; ATOX group (Acute arterial occlusion with ischemia) and ATOS group (claudication symptoms). Baseline characteristics and treatment details were extracted from electronic patient files. A telephone survey was conducted to collect patients’ follow-up data including a functional disability score using the Quick Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire. The primary endpoint of this study was symptom-free survival. Secondary endpoints were median QuickDASH scores during follow-up, postoperative complications and possible re-interventions. RESULTS A total of 20 patients (mean age 44.6 years, median follow-up 50.5 months) were included and divided into two groups (ATOX N=9, ATOS N=11). In the ATOX group, eight patients were primarily treated with catheter directed thrombolysis (CDT; N=5) or surgical thrombectomy (N=3). All patients received staged thoracic outlet decompression surgery (TOD). In the ATOS group, 10 patients primarily received TOD and one patient was treated conservatively with physiotherapy. Seven ATOX patients and nine ATOS patients were symptom free at follow-up with a median QuickDASH score of 2.3 (IQR 12.5) and 2.3 (IQR 16.5) respectively. Ten complications occurred in the ATOX group; three bleeding complications, five re-occlusions, one arterial dissection and one occipital infarction. In the ATOS group five complications occurred; one perioperative bleeding complication, three re-occlusions and a stent fracture. Seven versus five re-interventions were required in the ATOX and ATOS groups respectively. CONCLUSION The mid-term self-reported symptom free survival in both the ATOX as well as ATOS group seems acceptable while median QuickDASH scores in both groups indicate a very good functional outcome. This however comes at the cost of treatment related bleeding complications in especially the ATOX group presumably due to thrombolysis, and re-interventions required in almost one out of three patients.